Efeitos antiespasmódico e miorrelaxante do β-citronelol em músculo liso traqueal de ratos : potencial ação na hiperreatividade após desafio antigênico e elucidação do mecanismo de ação - Vasconcelos, Thiago Brasileiro de (2013)
The β-citronellol is an alcoholic monoterpene of natural occurrence that is found in several essential oils, including the citronella oil (obtained from Cymbopogon winterianus). In general, it is widely used as insect repellent. Recently this molecule has been studied as antibacterial, antifungal, antispasmodic, hypotensive and vasorelaxant agent. We aimed to study the effects of β-citronellol on smooth muscle contractility of rat airways. The animals were divided in four groups namely Control, Sensitized, Challenged and Treated. Isometric recordings were obtained from isolated preparations from tracheal tissues cut as rings. Inhalation of β-citronellol (300 µM) before antigen (ovalbumin, OVA) challenge prevented development of tracheal hyperreactivity in response to K+ or ACh in tissues of OVA-sensitized animals. In vitro, the cumulative addition of β-citronellol (10 to 1000 µM) did not change basal tone in tracheal smooth muscle preparations. In tracheal rings pre-contracted with K+ or acetylcholine (ACh), the addition of β-citronellol fully relaxed (p < 0.001, Two-Way ANOVA, Holm-Sidak) tracheal rings with IC50 values of 120.44 [73.29 – 197.91] µM for K+ and 211.10 [114.13 - 390.46] µM for ACh. The relaxing effect of β-citronellol was not altered (p > 0.05, Mann-Whitney test) after treatment with propranolol, N (G)-nitro-L- arginine methyl ester (L-NAME), tetraethylammonium (TEA), methylene blue, sodium orthovanadate, capsazepine, indomethacin and A-967079. Experiments performed in Ca2+ depleted medium containing EGTA revealed that low concentrations of β-citronellol preferentially inhibited contractions induced by recruiting Ca2+ influx via voltage-operated channels (VOC), although at higher concentrations it could also inhibit either on contractions evocked with receptor-operated (ROC) or store-operated (SOC) pathways. Such effect was supported by the more pronounced inhibitory effects of β-citronellol (p < 0.001, Two-Way ANOVA, Holm-Sidak) against contractions promoted in tracheal tissues maintained in Ba2+-containing medium. β-Citronellol also decreased the contractions induced by electrical field stimulation. These results suggest that β-citronellol has antispasmodic and myorelaxant properties on airway smooth muscle, which could be partly related to its ability in inhibiting the electromechanical coupling.